Inherited Tolerance in Cattle to the Apicomplexan Protozoan Theileria parva is Associated with Decreased Proliferation of Parasite-Infected Lymphocytes - Latre de Late, Perle; Cook, Elizabeth A. J.; Wragg, David; Poole, E. Jane; Ndambuki, Gideon; Miyunga, Antoinette Aluoch; Chepkwony, Maurine C.; Mwaura, Stephen; Ndiwa, Nicholas; Prettejohn, Giles; Sitt, Tatjana; Van Aardt, Richard; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Theileria parva is the causative agent of East Coast fever and Corridor disease, which are fatal, economically important diseases of cattle in eastern, central and southern Africa. Improved methods of control of the diseases are urgently required. The parasite transforms host lymphocytes, resulting in a rapid, clonal expansion of infected cells. Resistance to the disease has long been reported in cattle from T. parva-endemic areas. We reveal here that first- and second-generation descendants of a single Bos indicus bull survived severe challenge with T. parva, (overall survival rate 57.3% compared to 8.7% for unrelated animals) in a series of five field studies. Tolerant cattle displayed a delayed and less severe parasitosis and febrile response than unrelated animals. The in vitro proliferation of cells from surviving cattle was much reduced compared to those from animals that succumbed to infection. Additionally, some pro-inflammatory cytokines such as IL1β, IL6, TNFα or TGFβ which are usually strongly expressed in susceptible animals and are known to regulate cell growth or motility, remain low in tolerant animals. This correlates with the reduced proliferation and less severe clinical reactions observed in tolerant cattle. The results show for the first time that the inherited tolerance to T. parva is associated with decreased proliferation of infected lymphocytes. The results are discussed in terms of whether the reduced proliferation is the result of a perturbation of the transformation mechanism induced in infected cells or is due to an innate immune response present in the tolerant cattle.